1971
DOI: 10.1111/j.1365-2028.1971.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Elephant Ecology in the Queen Elizabeth National Park, Uganda

Abstract: Summary1. Aerial and ground counts in the Queen Elizabeth National Park from 1963 to 1969 indicate that the number of elephants has more than doubled. The increase appears to be the result of immigration rather than reproduction.2. Elephant food habits were studied for 10 months in two areas of the Park. In the short‐grass/thicket area, browse intake rose markedly whenever the rainfall fell below 50 mm/month. In the tall‐grass area without thicket, herbs were eaten frequently during the rains and Cymbopogon gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
6

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 20 publications
1
63
0
6
Order By: Relevance
“…In each village the dominant ethnic group is drawn from the surrounding communities. As reported by Infield (1989), an ethnic group represented in most villages is Abanyanja -"the people who stay near water" with tribe divided into three clans as shown in Table 1. Government in 1952 gazetted QENP at a time when several fishing villages existed in the area were gazette.…”
Section: Population Living Adjacent To the Lake George Wetlandsmentioning
confidence: 99%
See 2 more Smart Citations
“…In each village the dominant ethnic group is drawn from the surrounding communities. As reported by Infield (1989), an ethnic group represented in most villages is Abanyanja -"the people who stay near water" with tribe divided into three clans as shown in Table 1. Government in 1952 gazetted QENP at a time when several fishing villages existed in the area were gazette.…”
Section: Population Living Adjacent To the Lake George Wetlandsmentioning
confidence: 99%
“…A decision was made to allow these existing enclave villages to remain. Lake George supported a significant artisanal Fishing industry and indeed, these Lake was reported as one of the most productive inland waters for fisheries in Africa which could not be left unexploited (Infield, 1989).…”
Section: Population Living Adjacent To the Lake George Wetlandsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the deciduous savanna (Table 4). This indicates that a change in species abundance due to elephant browsing may not only be the result of preferential selection by elephants (Field 1971, Guy 1981, Jachmann & Croes 1991, Lewis 1991, Vesey-FitzGerald 1973a, but also the result of the differing ability of tree species to respond to damage by coppicing (see also Barnes 1983a).…”
Section: Intermediate Sized Treesmentioning
confidence: 99%
“…In wet season, grasses constitute 70% of elephant diet, but progressively shift to more browse proportion in dry season [25]. This is probably because grasses tend to rapidly become fibrous as dry season progresses, thereby diluting the nutrient content and therefore elephants turn to browse which is a critical dry season food reserve as its crude content is then higher than that of grasses [14] [26] [27]. Furthermore, Guy [21] [22] and Barnes [23] indicated that debarking of trees by elephants frequently occurs during late dry season when there is increased nutrient translocation from roots to new foliage and flowering parts.…”
Section: Factors and Mechanisms Of Woodland Conversionmentioning
confidence: 99%